Transformasi Khotbah Digital sebagai Tanggung Jawab Teologis Gereja di Era Modern - Yustinus Yustinus (Sekolah Tinggi Teologi Sriwijaya, 2025)
This study aims to affirm digital preaching as a theological mandate of the church in the digital era, rooted in the Great Commission and the Missio Dei. The research is motivated by a gap in previous studies that primarily focused on the technical and communicative aspects of digital ministry, without adequately framing them within the church’s theological responsibility. Employing a descriptive qualitative method through a literature-based approach in practical theology and digital media, this study finds that digital preaching plays a strategic role in strengthening the faith of believers, preserving doctrinal purity, and expanding the church’s mission in a contextual manner within online spaces. The findings reveal that social media is not merely a technological adaptation tool, but a new missional arena where the church can embody God’s truth and love in relevant ways for the digital generation. Practically, the study recommends that churches develop sustainable digital ministry strategies that balance theological depth with communicative effectiveness. Hence, digital preaching is understood not only as a medium of spiritual communication but also as a missional and contextual practice of practical theology for the church today and in the future.